Refleksi Balanced Scorcard Diagnostics pada Analisis Kelayakan Investasi secara Finansial - Rivai, Akhmad (Universitas Brawijaya, Indonesia, 2008)
Organizationally, high fund investation business which is its return exceed one year operate period are urgenly require financial invesment elegibility analysis that rely on the common standard. To stronger the framework in reality required applying operation performance methods by reflecting Balanced Scorcard Diagnostics (BSD). In long term, harmonious solidarity between finansial measure, consumer behavior, internal business, and also the business's growth itself, through goals and its realitation are expected to be happen to reach the company's goals.